Cell Therapy With Human ESC-Derived Cardiac Cells: Clinical Perspectives - Menasché, Philippe (Frontiers in Bioengineering and Biotechnology, 2020)
In the ongoing quest for the “ideal” cell type for heart repair, pluripotent stem cells (PSC) derived from either embryonic or reprogrammed somatic cells have emerged as attractive candidates because of their unique ability to give rise to lineage-specific cells and to trans-plant them at the desired stage of differentiation. The technical obstacles which have initially hindered their clinical use have now been largely overcome and several trials are under way which encompass several different diseases, including heart failure. So far, there have been no safety warning but it is still too early to draw definite conclusions regarding efficacy. In paral-lel, mechanistic studies suggest that the primary objective of “remuscularizing” the heart with PSC-derived cardiac cells can be challenged by their alternate use as ex vivo sources of a bio-logically active extracellular vesicle-enriched secretome equally able to improve heart function through harnessing endogenous repair pathways. The exclusive use of this secretome would combine the advantages of a large-scale production more akin to that of a biological medication, the likely avoidance of cell-associated immune and tumorigenicity risks and the possibility of intravenous infusions compatible with repeated dosing.